Current approaches in the treatment of catheter-related deep venous thrombosis in children. Issue 6 (2nd June 2020) - Jaffray, Julie; Goldenberg, Neil
ABSTRACT: Introduction: Acutely ill and medically complex pediatric patients typically rely on central venous catheters (CVCs) for vascular access. CVCs can have serious complications, including venous thromboembolism (VTE). In children, CVCs are the most common risk factor for VTE. Area covered: Studies focused on the prevention and treatment of CVC-related VTE in children have been lacking until recently. Currently, there is one U.S. Food and Drug Administration (FDA) approved anticoagulant, dalteparin, and phase 3 trial results for two direct oral anticoagulants (DOACs) in pediatrics have recently been published. This review focuses on the epidemiology, risk factors, prevention, and treatment for CVC-related VTE in children. Data are included from relevant articles in PubMed, 1990 to present. Expert opinion: With a paucity of FDA-approved anticoagulants for VTE treatment or prophylaxis in children, dosing and monitoring recommendations are often based largely on adult studies. DOACs are a promising group of anticoagulants to be used for children since they are given orally and do not require monitoring. Currently, children at the highest risk for CVC-related VTE are not well represented in the published pediatric DOAC trials.